Detection and molecular characterization of verotoxin in enteropathogenic Escherichia coli and non-O157 diarrheagenic Escherichia coli - Hasan Maziz, Mohammad Nazmul (Malaysian Journal of Science, 2005)
Detection and molecular characterization of verotoxin in enteropathogenic Escherichia coli and non-O157 diarrheagenic Escherichia coli